Using podcasts to bridge the gap between science communication and specialized scientific fields: a case study of mass spectrometry - Rehman, Nayyer; Edkins, Victoria; Ogrinc, Nives (Frontiers in Communication, 2024)
This study aimed to evaluate the use of podcasts in disseminating specialized scientific fields, such as mass spectrometry. Four podcasts featuring interviews with researchers working with mass spectrometry were produced. A mixed methods approach, comprising questionnaires and interviews, was used to gather listener feedback. Findings indicate that audience engagement is affected by factors like familiarity with science and relatability in content; therefore, to attract a wider audience, content must be presented to balance technical aspects with real-life examples to which listeners can relate. These findings will benefit researchers and stakeholders seeking to disseminate complex scientific topics using podcasts.